From commensalism to parasitism within a genus-level clade of barnacles - Watanabe, H. K.; Uyeno, D.; Yamamori, L.; Jimi, N.; Chen, C. (Biology Letters, 2023)
Understanding how animals evolve to become parasites is key to unravelling how biodiversity is generated as a whole, as parasites could account for half of all species richness. Two significant impediments to this are that parasites fossilize poorly and that they retain few clear shared morphological features with non-parasitic relatives. Barnacles include some of the most astonishingly adapted parasites with the adult body reduced to just a network of tubes plus an external reproductive body, but how they originated from the sessile, filter-feeding form is still a mystery. Here, we present compelling molecular evidence that the exceedingly rare scale-worm parasite barnacle Rhizolepas is positioned within a clade comprising species currently assigned to Octolasmis, a genus exclusively commensal with at least six different phyla of animals. Our results imply that species in this genus-level clade represent an array of species at various transitional stages from free-living to parasitic in terms of plate reduction and host-parasite intimacy. Diverging only about 19.15 million years ago, the route to parasitism in Rhizolepas was associated with rapid modifications in anatomy, a pattern that was likely true for many other parasitic lineages.
The host taxon genus, Laetmonice, is misspelled at every usage as Laetomonice [sic]